2005
DOI: 10.1073/pnas.0501606102
|View full text |Cite
|
Sign up to set email alerts
|

Color-blind fluorescence detection for four-color DNA sequencing

Abstract: We present an approach called pulsed multiline excitation (PME) for measurements of multicomponent, fluorescence species and demonstrate its application in capillary electrophoresis for DNA sequencing. To fully demonstrate the advantages of PME, a fluorescent dye set has been developed whose absorption maxima span virtually the entire visible spectrum. Unlike emission wavelength-dependent approaches for identifying fluorescent species, the removal of the spectral component in PME confers a number of advantages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Xue and Yeung used two‐color (488 nm and 514 nm) excitation system for fluorescence detection in DNA sequencing by capillary‐array electrophoresis . Furthermore, Lewis et al also reported the multicolor detection for DNA sequencing based on the pulsed multiline (399 nm, 488 nm, 594 nm, and 685 nm) excitation . In this literature, minimized crosstalk matrix achieved to 0.01 was found in BigDye v3.1‐labeled terminator at 530 nm and 560 nm detection windows.…”
Section: Introductionmentioning
confidence: 99%
“…Xue and Yeung used two‐color (488 nm and 514 nm) excitation system for fluorescence detection in DNA sequencing by capillary‐array electrophoresis . Furthermore, Lewis et al also reported the multicolor detection for DNA sequencing based on the pulsed multiline (399 nm, 488 nm, 594 nm, and 685 nm) excitation . In this literature, minimized crosstalk matrix achieved to 0.01 was found in BigDye v3.1‐labeled terminator at 530 nm and 560 nm detection windows.…”
Section: Introductionmentioning
confidence: 99%
“…Some methods that have been used to perform color-blind detection in microfluidic systems include pulsed multiline excitation, 22 discrimination by fluorescence lifetimes, 23 dual point excitation, 24 and frequency encoding. 25,26 In frequency encoding, the fluorescence from individual dyes are encoded by pulsing multiple lasers at non-harmonic frequencies of one another and collecting all fluorescence emission onto a single detector.…”
Section: Introductionmentioning
confidence: 99%
“…(C) Transformation of the raw trace data derived from the experiment described in B into readable, DNA sequence data using mobility software correction. Reprinted with permission from National Academy of Sciences, U.S.A. © 2005, Lewis et al 2005.…”
Section: Pyrosequencingmentioning
confidence: 99%
“…Recently, Lewis et al (2005) described a simple but effective method for multifluorescence discrimination called pulsed multiline excitation (PME). The underlying principle of this fourlaser system is the correlation of sequential laser pulses with detector response ( Fig.…”
Section: Fluorescence Detectionmentioning
confidence: 99%
See 1 more Smart Citation